Efeito de alguns fenos de origem tropical sobre o crescimento de frangos de corte - Ochiai, Takeshi; Campos, Joaquim; Brandão Fonseca, José (Revista Ceres, 2025)
An experiment was conducted with a total of 400 broilertype chicks to study some tropical hays as a substitute for alfalfa meal in chick starter rations. The chicks were fed diets containing 5 percent either of one of the following products: alfalfa hay, ramie (Boehmeria nivea) meal, "soja perene" hay (Glycine javanica) and tarsum (a natural source of vitamins, microelements and pigments). Corn cobs was used in the control diet.